The Questions of Medical Informatics - Dimitrov, I. (Methods of Information in Medicine, 1996)
Each science is identified with the questions it raises with respect to its object of study. This paper discusses the formulation of the basic questions of medical informatics. From a historical point of view, it first dealt with the problems of medical computing. Thereby, three classical questions arose: How can existing computers and information technologies assist in medical activities? Which components of the mathematical apparatus of informatics can be used for solving medical problems, and how and what activities of a physician are subject to algoritmization? The present time raises a new circle of questions centered around the basic one: How is the information system of the human organism structured and how does it function? This question and others form the basis of a new trend in medical informatics.
Keywords: Medical Informatics